2006
DOI: 10.3200/jach.54.4.231-237
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the Sleep Treatment and Education Program for Students (STEPS)

Abstract: University students report significantly worse sleep quality than the general population. Sleep problems are related to increased health concerns, irritability, depression, fatigue, and attention and concentration difficulties, along with poor academic performance. Clinical research indicates that psychoeducational interventions are among the most effective methods for improving sleep quality in the general population. Similar studies for university students are lacking. In this study, the authors describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
124
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 39 publications
15
124
3
6
Order By: Relevance
“…Although many students in both groups indicated on questionnaire that they had made changes in their behavior, our study did not obtain objective data (e.g., actigraphy) that this actually occurred. Nevertheless, our study is consistent with the observations by Brown et al, 20 who found in a small randomized controlled study of college psychology students that a short sleep hygiene program consisting of a brief oral presentation and handouts could improve sleep hygiene practices and sleep quality. Importantly, our findings extend their results by demonstrating similar results using Internet technology in a larger cohort.…”
supporting
confidence: 82%
“…Although many students in both groups indicated on questionnaire that they had made changes in their behavior, our study did not obtain objective data (e.g., actigraphy) that this actually occurred. Nevertheless, our study is consistent with the observations by Brown et al, 20 who found in a small randomized controlled study of college psychology students that a short sleep hygiene program consisting of a brief oral presentation and handouts could improve sleep hygiene practices and sleep quality. Importantly, our findings extend their results by demonstrating similar results using Internet technology in a larger cohort.…”
supporting
confidence: 82%
“…Brown and colleagues found improved sleep quality (PSQI scores) with a single group 30-minute sleep-health education program in a general population college sample. 34 It may be that the group of students studied by Brown and colleagues 34 had sleep distress at baseline (mean PSQI = 7.3 among intervention group participants and 6.6 among controls) comparable to our sample of students with sleep problems (mean PSQI = 7.7 for Refresh participants and 7.5 for Breathe participants) and different from our group of participants without significant baseline sleep problems (mean PSQI = 3.3 for Refresh participants and 3.5 for Breathe participants). It seems reasonable to expect that students with disturbed sleep at baseline may benefit most from a program designed to help them improve their sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Students should understand the effects of caffeine, alcohol, napping, varied sleep schedules, and exercise on sleep problems . Evidence demonstrates that in a population without sleep disturbances, this strategy increases knowledge of sleep hygiene which results in better sleep practices and consequently better sleep quality (Brown, Buboltz, & Soper, 2006;Brown, Buboltz, & Soper, 2002).…”
Section: Discussionmentioning
confidence: 99%